Analytical Method Development and Validation of Stability Indicating Rp-Hplc Method for The Simultaneous Estimation of Ombitasvir, Paritaprevir and Ritonavir - lakshmi, G.Sai sri; I, Somasundaram (Journal of Neonatal Surgery, 2025)
Special, effective high pressure liquid chromatography method has been developed for the simultaneous quantification of Ombitasvir and Paritaprevir.By using Waters HPLC e-2695 quaternary pump with a PDA detector of 2998 instrument the chromatographic separation of Ombitasvir,Paritaprevir and Ritonavir was achieved on the column of X-bridge phenyl150x4.6mm, 3.5µ using an isocratic elution with a buffer containing 0.1percenttriethyl amine and acetonitrile at a rate of 50:50 as a mobile phase with a flow rate of 1 ml/min at ambient temperature. A detector wavelength of 254 nm utilizing the PDA detector were given in the instrumental settings. The linearity was studied between the concentration range of 3.13-18.75 µg/ml of Ombitasvir,18.75-112.5 µg/ml of Paritaprevir and 12.5-75 µg/ml of Ritonavir were injected.The plotted calibration curves were linear with a regression coefficient of R2> 0.999, indicates that the linearity was with in the limit. As a part of method validation the parameters like specificity, linearity, accuracy, ruggedness, robustness were determined and the results were found to be within the allowable limit. The method developed was found to be applicable to routine analysis and to be used for the measurement of both active pharmaceutical ingredients (i.e, Ombitasvir,Paritaprevir and Ritonavir).Validation of the proposed method was carried out according to an International Conference on Harmonization (ICH) guidelines.